Penguatan Dinamika Kelompok Siswa melalui Nilai Kerja Sama pada Pembelajaran Matematika di Sekolah Dasar: Perspektif Pendidikan Islam - Lubis, Namiroh; Soraya, Arafatul; Prasetyo, Sigit; Putri, Fia Alifah; Iskandar, Wahyu (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research examines integrating cooperative values ​​in Islam and mathematics learning in elementary schools. This study combines descriptive and qualitative methods with a literature study approach. Data was collected from various scientific papers, books, journal articles, and relevant internet sources. This research aims to identify how cooperative values ​​are applied in mathematics learning and analyze their influence on student group dynamics. The research results show that applying cooperative values ​​can increase student activity in learning, improve student attitudes and skills, and enrich their learning experience. The main challenge faced is the readiness of teachers to implement this approach and the necessary curriculum adjustments. Appropriate support for teachers and adaptation of teaching materials are key factors in successfully integrating cooperative values ​​in mathematics learning.